2014
DOI: 10.1177/1470320314553984
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CYP11B2-344T>C polymorphsim and atrial fibrillation: A meta-analysis

Abstract: Our pooled data suggest a significant association exists between CYP11B2-344T>C polymorphism and AF among hypertension populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The role of the CYP11B2-344C/T polymorphism in the risk of developing AF has been reported in Chinese populations (Li et al, 2012;Lu et al, 2015). Similarly, other studies have shown that the CYP11B2-344C/T polymorphism is associated with AF in patients with heart failure (Amir et al, 2008) and hypertension (Fu et al, 2015). By contrast, Sun et al (2011) reported a lack of any association between this polymorphism and AF in a Chinese population.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The role of the CYP11B2-344C/T polymorphism in the risk of developing AF has been reported in Chinese populations (Li et al, 2012;Lu et al, 2015). Similarly, other studies have shown that the CYP11B2-344C/T polymorphism is associated with AF in patients with heart failure (Amir et al, 2008) and hypertension (Fu et al, 2015). By contrast, Sun et al (2011) reported a lack of any association between this polymorphism and AF in a Chinese population.…”
mentioning
confidence: 77%
“…Likewise, a study by Amir et al (2008) found a significant relationship between this polymorphism and clinical AF. In addition, research has revealed that the CYP11B2-344C/T polymorphism is associated with AF in Chinese patients with hypertension (Fu et al, 2015) and in African Americans with heart failure (Bress et al, 2013). However, previous work failed to confirm this association between the CYP11B2-344C/T polymorphism and the incidence of AF in Chinese patients (Hou et al, 2017;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several meta-analyses of gene polymorphisms and AF susceptibility have been published and have identi ed associations, including chromosome 4q25 variants, CYP11B2 -344T>C, and mink S38G [40][41][42][43]. A growing number of studies have identi ed polymorphisms in both ZFHX3 and PRRX1, although they have not been reported through meta-analysis studies that could clarify their associations with AF susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several meta-analyses about gene polymorphisms and AF susceptibility have been published: such as chromosome 4q25 variants, CYP11B2 -344T>C, mink S38G, and so on [40][41][42][43]. A growing number of papers have pointed to polymorphisms from both ZFHX3 and PRRX1 genes.…”
Section: Discussionmentioning
confidence: 99%